(untitled) (Research, Society and Development, 2020)
Dealing with the Covid-19 pandemic is playing a significant role in public health policies around the world. Mental health is one. Either in supporting the maintenance of isolation or dealing with demands, which may come from the general population and health professionals. This work presents a compilation of data obtained by clinical psychologists during the Covid-19 pandemic in Brazil. Through searches on social media with #Covid19 and #MentalHealth and the exchange of information on networks of professionals, it was possible to compile and group the main psychological symptoms presented during isolation. Information was clustered according to the period it appeared, in order to guide future situations. Moreover, to prepare a group of clinical psychologists to provide online assistance. Prevention must be the key to deal with the mental health catastrophe that there is to come.